Stapled Hemorrhoidopexy: “Mucosectomy or Not Only Mucosectomy, This Is the Problem” - Eberspacher, Chiara; Magliocca, Fabio M.; Pontone, Stefano; Mascagni, Pietro; Fralleone, Lisa; Gallo, Gaetano; Mascagni, Domenico (Frontiers in Surgery, 2021)
Introduction: Stapled haemorrhoidopexy was originally defined as a rectal mucosectomy. The aims of our retrospective single-single center study were, primarily, to demonstrate if the excised specimen comprises only mucosa or more wall rectal layers and, secondarily, if the latter excision should be considered a technical mistake with an increase in complications. Material and Methods: We hystopathologically analysed surgical samples from patients who underwent stapled haemorrhoidopexy performed between 2014 and 2019. Patients were divided in three Groups, according to the stapler used: Group A (Single PPH®); Group B (Double PPH®); Group C (CPH34HV™). We evaluated the actual wall layers included in the stapled rectal ring. For every specimen, we reconstructed the history of the corresponding patient and the incidence of complications. Results: Of the 137 histological slides available, 13 were only mucosectomies (9.5%) and 124 presented also submucosa and muscularis propria (90,5%) - 50/58 patients in Group A, 28/28 in Group B and 46/51 in Group C -. Evaluating our second aim, no statistically significant difference in the rate of complications were found, when stratifying patients according to the thickness of the resection (mucosectomy -M- or “full thickness” -FT-). Discussion: Stapled haemorrhoidopexy is not a simply mucosectomy, but a resection of the rectal wall with almost all its layers. This concept of a “full-thickness” specimen defines the entity of this operation and exclude a direct correlation with an increased rate of complications.